2015
DOI: 10.1016/j.bbacli.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of carbohydrate counting and insulin dose calculations in paediatric patients with type 1 diabetes mellitus

Abstract: BackgroundPatients with type 1 diabetes mellitus (T1DM) who are able to adjust their insulin doses according to the carbohydrate content of a meal, as well as their blood glucose, are likely to have improved glycaemic control (Silverstein et al., 2005). With improved glycaemic control, patients have a lower risk of developing long-term microvascular complications associated with T1DM (Diabetes Control and Complications Trial Research Group, 1993).To assess the carbohydrate and insulin knowledge of patients att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…To our knowledge, there have been only three previous studies examining CHO counting accuracy in the adolescent age range using commonly eaten food items, [13][14][15] and one recent study investigating CHO counting knowledge through PCQ scores in a clinic population. 24 Two American studies, using similar methodology to our study, found that 23% and 55% of adolescents tested were accurate within 10 g. 13,15 The study demonstrating the highest rate of inaccuracy had a small sample (n = 49) and may not, therefore, have been representative of the broader clinic population. A study from Australia, using varying methods of CHO estimation (1 g increments, 10 g portion sizes, 15 g exchanges) found that 43% were accurate within 5 to 7 g and 73% within 10 to 15 g. 14 A notable difference in this study is that the participants included parents.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…To our knowledge, there have been only three previous studies examining CHO counting accuracy in the adolescent age range using commonly eaten food items, [13][14][15] and one recent study investigating CHO counting knowledge through PCQ scores in a clinic population. 24 Two American studies, using similar methodology to our study, found that 23% and 55% of adolescents tested were accurate within 10 g. 13,15 The study demonstrating the highest rate of inaccuracy had a small sample (n = 49) and may not, therefore, have been representative of the broader clinic population. A study from Australia, using varying methods of CHO estimation (1 g increments, 10 g portion sizes, 15 g exchanges) found that 43% were accurate within 5 to 7 g and 73% within 10 to 15 g. 14 A notable difference in this study is that the participants included parents.…”
Section: Discussionsupporting
confidence: 55%
“…The mean score for CHO estimation was lower than ours at 68%. Differences in this study included primarily parental participation (82.7%) and a smaller sample size ( n = 81) . A further issue is that the PCQ has only been validated in a North American population, and differences in common foods eaten may lead to falsely low scores due to unfamiliarity with the food item.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study population less than 1/3 rd had good knowledge about carbohydrate counting, with nearly 69.5% either over/underestimating the carbohydrate values in the meal. Previous studies from western developed countries such as USA and Ireland have demonstrated better carbohydrate counting knowledge among parents [ 11 , 18 ]. The observed difference could be due to the better socioeconomic status and health literacy in these countries, in comparison to Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…Pump bolus wizards are easier to use. In addition, it appears that children on IP have a better knowledge of CC than patients on SII (21).…”
Section: Discussionmentioning
confidence: 97%